Incretin mimetics and drugs increasing the level of endogenous incretins in the treatment of type 2 diabetes mellitus - Czech, Anna (Przewodnik Lekarza/Guide for GPs, 2009)
The term incretins relates to the following intestinal hormones: GLP-1 (glucagon-like peptide-1) and GIP (glucose-dependent insulinotropic peptide). They are responsible for 50-60% of insulin secretion. In type 2 diabetes the secretion of these hormones is diminished. In order to treat such disorders in type 2 diabetes, analogues of GLP-1 acting analogously as endogenous GLP-1 and drugs inhibiting the activity of DPP-IV (dipeptidyl peptidase IV) are introduced. In the treatment of type 2 diabetes these drugs are used as a monotherapy or a combined therapy either with metformin or sulfonylureas.